Breaking Cultural “Taboos” About the Body and Gender: Brazilian Students’ Emancipation From a Thematic Perspective of School Physical Education - Lima, Cyntia Emanuele Souza; Ferreira, Emmanuelle Cynthia da Silva; Sanches Neto, Luiz; Venâncio, Luciana (Frontiers in Education, 2020)
In order to understand the problems related to equity and diversity, we can first recognize that school physical education potentializes processes of a cultural context that has, directly and indirectly, interfered with the body and its relationships. We live in a still retrograde society, which has its foundations established in hierarchical relations of power and that women are often devalued in many sectors, especially in contexts of deep social exclusion. However, the body is the result of cultural construction and the concept of “natural” coexists within the culture. Then, it is necessary to problematize and (de)construct concepts that reinforce prejudiced/discriminatory attitudes. Our objective in this article is to interpret how high school students’ relationship to knowledge allows situated interventions on gender issues by undergraduate students from one physical education teacher education program. Methodologically, we used a qualitative approach to develop interventions in one high school in the city of Fortaleza, Ceará, Brazil, in two stages: i) questionnaire to consider the students’ knowledge related to gender issues; ii) intervention to work on issues of gender and social inequality. As a result, we have identified as essential to list such issues in the school environment, because it is in the school that we live the plurality of being and establish various social relations, locating them critically. We recognize that the challenge of intervention is beyond problematizing classes, but in educating students as autonomous and emancipated individuals as they can construct their own (self)critique. In conclusion from the analysis of those interventions, it was possible to strongly observe the existing hierarchical relations. In this sense, we emphasize the importance of the teacher to address thematics that generate learning with respect to the male and female bodies in the classes, so that there is a better understanding of the differences to foster the critical and emancipatory expansion of gender equality.